Hyperinvariant subspaces for some operators on locally convex spaces - Edvard Kramar (International Journal of Mathematics and Mathematical Sciences, 2000)
Some results concerning hyperinvariant subspaces of some operators on locally convex spaces are considered. Denseness of a class of operators which have a hyperinvariant subspace in the algebra of locally bounded operators is proved.